Distribution and identification of the genus Biomphalaria Preston (1910): important insights into the epidemiology of Schistosomiasis in the Amazon region - Lopes, Tatiane Alencar (2019)
Schistosomiasis is a disease transmitted by flatworms of the species Schistosoma mansoni (Sambon, 1907). The spread of the disease is dependent on the presence of snails of the genus Biomphalaria (intermediate hosts). In Brazil, while 11 species and one subspecies have been identified, only three ? B. glabrata, B. straminea and B. tenagophila ? are known to eliminate cercariae into the environment. However, only B. peregrina and B. amaz?nicaare susceptible to infection in the laboratory. Research on schistosomiasis and its intermediate hosts in Brazil is restricted to the country?s southern and southeastern regions, and little is known of the occurrence of Biomphalaria in the Amazon region, where the disease is probable endemic due to the ideal environmental conditions and the availability of hosts. Data on the occurrence of this genus are essential for epidemiological studies of schistosomiasis, given that the confirmation of its occurrence in a given region, and the correct identification of the species, are fundamental to the development of effective strategies for the prevention and control of schistosomiasis.